The Influence of Compensation, Competency and Workload on Employee Performance Surabaya Health Office with Job Satisfaction as an Intervening Variable - Wulandari, Dhian; Sukoco, Agus (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: The purpose of this research is to determine and analyze the influence of compensation on job satisfaction, competence on job satisfaction, workload on job satisfaction, compensation on employee performance, competence on employee performance, workload on employee performance, job satisfaction on employee performance, compensation on employee performance with job satisfaction as an intervening variable, competence on employee performance with job satisfaction as an intervening variable, and workload on employee performance with job satisfaction as an intervening variable at the Surabaya Health Office. Design/methodology/approach: This research uses quantitative data with data collection techniques using questionnaires via Google Form. The research population was all ASN of the Surabaya Health Office with a sample of 56 respondents taken using a simple random sampling technique. The data analysis method uses Structural Equation Modeling (SEM) based on Partial Least Square (PLS). Findings: The results showed that the compensation variable had an influence on job satisfaction, the competency variable had an influence on job satisfaction, the workload variable had an influence on job satisfaction, the compensation variable had no influence on employee performance, the competency variable had an influence on employee performance, the workload variable had no influence on employee performance, the job satisfaction variable had an influence on employee performance, the compensation variable had no influence on employee performance with job satisfaction as an intervening variable, the competency variable had no influence on employee performance with job satisfaction as an intervening variable, the workload variable had no influence on employee performance with job satisfaction as an intervening variable Paper type: Research paper